Analysis of regional environment and regional innovation strategy based on cybernetics. (October 2019) - Teng, Tangwei; Qin, Liuting
Abstract: In this paper, based on the perspective of carbon emissions, the regional environment and regional innovation strategies were analyzed by using cybernetics. The main idea was to calibrate the diesel engine simulation model with predictive function based on the data collected from the bench test, and then according to the simulation model, the genetic algorithm was applied to optimize the EGR parameters and fuel injection parameters with the target of emission generation and output torque. First of all, the combustion process and emission performance of diesel engine with internal exhaust re-circulation were studied by genetic algorithm, and the genetic algorithm model was constructed. Then, the genetic algorithm program was written based on Matlab. In addition, taking the NOx emission as the target, and the Soot emission and the output torque of the original machine as constraints, through the joint simulation of Matlab and GT-Power, the EGR parameters and fuel injection parameters of the 10% to 50% load conditions were optimized at the speed of 1500 r/min and 2000 r/min. Finally, the validity of this method was verified and analyzed.